Ответы 1

  •  \frac{2 {x}^{2} }{ {x}^{2}  - 4}  -  \frac{2x}{x + 2}  =   \\  = \frac{2 {x}^{2} }{ (x + 2)(x - 2)}  -  \frac{2x}{x + 2}  =  \\  =  \frac{2 {x}^{2}  - 2x \times (x - 2) }{(x + 2)(x - 2)}  =  \\  =  \frac{2 {x}^{2}  - 2 {x}^{2}  + 4x }{(x + 2)(x - 2)}  =  \frac{4x}{ {x}^{2}  - 4}

    • Автор:

      rylee98
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years